Clays and Clay Minerals, Vol. 56, No. 4, 397–403, 2008. - Cui, Haojie; Liu, Xiangwen; Tan, Wenfeng; Feng, Xionghan; Liu, Fan; Ruan, Huada Daniel (The Clay Minerals Society, 2008)
Todorokite is a commonMn oxide mineral in terrestrial and ocean-floor environments, and it is commonly synthesized from layered Na-buserite. Pyrophosphate, which is known to form strong complexes with Mn(III) at a pH range of 1-8, was added to a suspension of Na-buserite in order to sequester the available Mn(III) in Na-buserite. No Mn(III)-pyrophosphate complex was formed in solution at pH 10, and the treated Na-buserites were converted completely to todorokite. Significant transformation reductions were observed when Na-buserite was treated with pyrophosphate solution at pH 7. The presence of Mn(III) within the MnO6 octahedral sheets of Na-buserite is critical for the transformation from layered buserite to tunnel-structured todorokite at atmospheric pressure. At lower pH, two effects are combined to reduce the amount of Mn(III) in the layers: (1) the complexing power of pyrophosphate is increased; and (2) the transformation from Na-buserite to H-birnessite, which is concomitant with the migration of Mn(III) from layers to the interlayer, and the partial disproportionation of Mn(III). The results showed that Mn(III) played a key role in the transformation of layered Na-buserite to tunnel-structured todorokite at atmospheric pressure.
Influence Of Mn(iii) Availability On The Phase Transformation From Layered Buserite To Tunnel-structured Todorokite.
Clays and Clay Minerals, Vol. 56, No. 4, 397–403, 2008. Influence Of Mn(iii) Availability On The Phase Transformation From Layered Buserite To Tunnel-structured Todorokite. Haojie Cui; Xiangwen Liu; Wenfeng Tan; Xionghan Feng; Fan Liu; Huada Daniel Ruan. DOI: 10.1346/CCMN.2008.0560401. Copyright © 2008, The Clay Minerals Society.
Keywords: Periodicals; Geology; Buserite; Mn Oxide; Todorokite; Transformation; Refluxing